THE IMPACT OF IMPLEMENTING GREEN ECONOMY PRINCIPLES ON REGIONAL ECONOMIC GROWTH IN SAMARKAND REGION - Azizbek Lapasov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article provides a comprehensive analysis of the implementation of green economy principles in the Samarkand region and their impact on regional economic growth. The study examines practical initiatives in areas such as the use of renewable energy sources, waste management, ecological tourism, and green transport. The influence of green economy measures on regional economic indicators is assessed using statistical and systematic approaches. Based on international experience, the article presents proposals and recommendations for promoting the green economy in the Samarkand region. The findings of the research serve as a foundation for evidence-based decision-making in the development of regional growth strategies.